Terahertz Circular Dichroism Spectroscopy of 3D Chiral Metallic Microstructures Fabricated Using High Precision CNC Machining - Atsushi Ouchi; Saroj R. Tripathi (IEEE Journal of Microwaves)
Recent advancements in terahertz wave applications for sensing, imaging, and high-speed communication have spurred a substantial demand for low-cost, easily accessible optical components capable of manipulating terahertz wave polarization. In this study, terahertz circular dichroism spectroscopic measurements of micrometer-sized metallic chiral helix arrays, fabricated using computer numerical control (CNC) machining, are presented. Experimental results demonstrate a giant circular dichroism of ±0.6 in an axial mode of operation for left- and right-handed arrays within a sub-terahertz frequency range. The helix array converts linearly polarized light into circularly polarized light from 120 GHz to 200 GHz, with a 3 dB axial ratio relative bandwidth approaching 50%. The polarization extinction ratio is in excess of 20 dB. These outstanding features, combined with their low cost, high accessibility, as well as their potential for mass production, pave the way for development of diverse range of optical components such as polarizers, filters, absorbers, and isolators operating in the terahertz frequency region.